A review of the subgenus Mesolethrus Nikolajev, 2003 of the genus Lethrus Scopoli, 1777 (Coleoptera: Geotrupidae: Lethrinae) with description of a new species - Shapovalov, Andrey M.; Bagaturov, Mikhail F. (Zootaxa, 2023)
A review of the subgenus Mesolethrus Nikolajev, 2003, with diagnostic characters, distribution data and a key to the species is provided. Lethrus (Mesolethrus) dyonini A. Shapovalov & Bagaturov, new species, is described from Uzbekistan (Tashkent Region). Lethrus (Mesolethrus) shakhristanicus Nikolajev, 2003 is recorded for the first time from Kyrgyzstan and Uzbekistan. Previous records of L. (M.) inermis Reitter, 1866 from Kyrgyzstan are considered erroneous.